Examining the Relationship between Tourist Motivation, Touristic Attractiveness, and Revisit Intention - Ella Anastasya Sinambela (Journal of Social Science Studies (JOS3), 2021)
The tourism industry is considered to be one of the largest and fastest growing industries in the world and greatly influences the economy. In this industry, development is determined by the decision to visit tourist attractions and the intensity of visits from tourists. In this study, tourist motivation and touristic attractiveness variables will be observed that contribute to the interest in revisiting tourist attractions. Tourist motivation is an integral part of travel behavior and has been widely researched and applied in tourism marketing strategies. While touristic attractiveness is seen as the main element to attract investors and visitors. For visitors, attraction is a reflection of the feelings, beliefs, and opinions an individual has about the ability of a given destination to meet that person's particular holiday needs. The sample of this study amounted to 100 respondents who were collected by convenience sampling method. This research uses multiple linear regression data analysis techniques. The results showed that tourist motivation had a significant effect on revisit intention. Touristic attractiveness has a significant effect on revisit intention. Touristic attractiveness is a variable that has a dominant influence and it becomes a tough task for managers to keep making tourist destinations amidst competition in the tourism industry.